2010
DOI: 10.1021/la904293f
|View full text |Cite
|
Sign up to set email alerts
|

On the Characteristics of Ion Implanted Metallic Surfaces Inducing Dropwise Condensation of Steam

Abstract: The present work provides new information on the characteristics of ion implanted metallic surfaces responsible for the adjustment of stable dropwise condensation (DWC) of steam. The results are based on condensation experiments and surface analyses via contact angle (CA) and surface free energy (SFE) measurements as well as scanning electron microscopy (SEM). For studying possible influences of the base material and the implanted ion species, commercially pure titanium grade 1, aluminum alloy Al 6951, and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Vapor condensation is a widespread natural phenomenon which includes the formation of mist and rain [1], the production of droplets on a cooling surface [2], and so on. It is also an important process in industries such as thermal management [3], water desalination [4], and refrigeration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vapor condensation is a widespread natural phenomenon which includes the formation of mist and rain [1], the production of droplets on a cooling surface [2], and so on. It is also an important process in industries such as thermal management [3], water desalination [4], and refrigeration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ionenstrahlimplantation [5] mit Stickstoff-, Kohlenstoff-, Sauerstoff-oder Argonionen bei unterschiedlichen Ionendosen und Implantationsenergien. Für Details zur Probenpräparation sei auf frühere Veröffentlichungen [6 -8] [7,8]. Die Analyse der mikroskopischen Oberflächenrauigkeiten erfolgte mit Hilfe der Rasterkraftmikroskopie (AFM-System Veeco Dimension 3100, Digital Instruments) sowie der Rasterelektronenmikroskopie (REM-System JSM-6400, JEOL).…”
Section: Experimentelle Methodenunclassified
“…where e is the surface energy, E represents modulus of elasticity, and a is a constant. However, Rausch et al [105] stated that it is not still very clear as to what characteristics of the ion-implanted surfaces made them feasible for DWC. In another study of ion implantation of N + ions on a titanium surface, the ability to achieve and sustain increased DWC was pointed out [106].…”
Section: Ion Implantationmentioning
confidence: 99%
“…Their results suggested that particulate precipitates caused inhomogeneity on the surface. This nanoscale roughness and surface chemical inhomogeneity helps in nucleating DWC and sustaining DWC even at increased wettability [105,107]. It was supposed that these precipitates were formed by supersaturation of the resultant ion-implanted surface with doping elements.…”
Section: Ion Implantationmentioning
confidence: 99%